FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT TBC PADA NELAYAN DI KAMPUNG NELAYAN SEBERANG LINGKUNGAN XII, KELURAHAN BELAWAN I, MEDAN - Fithri Handayani Lubis; Rizka Annisa (JURNAL KESMAS DAN GIZI (JKG), 2019)
The objective of the research was to analyze the influence of the characteristics of fishermen’s house on the incidence of pulmonary tuberculosis. The research used an analytic method with case-control design. The population was 90 fishermen, wih sample details 45 case and 45 control, taken by using consecutive sampling technique. The data were gathered by conducting interviews, questionnaires, observation, and measurement and analyzed by using univatriate analysis, bivatriate analysis, and multivatriate analysis at the significance level of 95%. The results of the study indicate that there is a relationship between variabel temperature (p-value : 0,004), humidity (p-value : 0,006) and mosquito coils (p-value : 0,044 with the incidence of pulmonary tuberculosis. Humidity variable has the highest Exp Value (B) = 8.4, so it assumed respondents who live in homes with not requirements humidity levels 8.4 times more easily infected with TBC. Kampung nelayan residents are expected to wear warm clothing at night and open windows every day. It is expected that Puskesmas Belawan will implement health program policies set by the government in reducing the incidence of pulmonary tuberculosis.